Lack of antiviral activity of darunavir against SARS-CoV-2 - Sandra De Meyer; Denisa Bojkova; Jindrich Cinatl; Ellen Van Damme; Christophe Buyck; Marnix Van Loock; Brian Woodfall; Sandra Ciesek (International Journal of Infectious Diseases, 2020)
Objectives: Given the high need and the absence of specific antivirals for treatment of COVID-19 (the disease caused by severe acute respiratory syndrome-associated coronavirus-2 [SARS-CoV-2]), human immunodeficiency virus (HIV) protease inhibitors are being considered as therapeutic alternatives. Methods: Prezcobix/Rezolsta is a fixed-dose combination of 800 mg of the HIV protease inhibitor darunavir (DRV) and 150 mg cobicistat, a CYP3A4 inhibitor, which is indicated in combination with other antiretroviral agents for the treatment of HIV infection. There are currently no definitive data on the safety and efficacy of DRV/cobicistat for the treatment of COVID-19. The in vitro antiviral activity of darunavir against a clinical isolate from a patient infected with SARS-CoV-2 was assessed. Results: DRV showed no antiviral activity against SARS-CoV-2 at clinically relevant concentrations (EC50 > 100 μM). Remdesivir, used as a positive control, demonstrated potent antiviral activity (EC50 = 0.38 μM). Conclusions: Overall, the data do not support the use of DRV for the treatment of COVID-19.